Developing progress monitoring measures: Parallel test construction from the item-up - Ketterlin-Geller, Leanne R.; Sparks, Anthony; McMurrer, Jennifer (Frontiers in Education, 2022)
Progress monitoring is a process of collecting ongoing samples of student work and tracking performance of individual students over time. Progress monitoring involves administering parallel sets of items to the same student on a regular basis (at least monthly) that are sensitive to changes in the student’s understanding based on instruction. The sets of items administered over time should be parallel in difficulty so that differences in performance can be attributed to differences in the student’s understanding as opposed to variability in item difficulty across sets. In this manuscript, we describe an approach to designing items that controls item-level variability by constraining the item features that may elicit different cognitive processing. This approach adapts the principles of Automated Item Generation (AIG) and includes carefully designing test specifications, isolating specific components of the content that will be assessed, creating item models to serve as templates, duplicating the templates to create parallel item clones, and verifying that the duplicated item clones align with the original item model. An example from an operational progress monitoring system for mathematics in Kindergarten through Grade 6 is used to illustrate the process. We also propose future studies to empirically evaluate the assertion of parallel form difficulty.